Carbon dioxide transformation as a green alternative to phosgene and chloroformates: N-carboxyalkylation of lactams and analogues. Issue 54 (December 2021) - Homerin, Germain; Nica, Adrian Sorin; Aitouche, Abdelouhab; Rigo, Benoît; Lipka, Emmanuelle; Ghinet, Alina
Graphical abstract: Highlights: New CO2 transformation technology at room temperature. CO2 is a green alternative to toxic phosgene and chloroformates to produce lactam carbamates. Access to new carbamate scaffolds for which corresponding chloroformates are not commercially available. Versatility of the protocol for lactams. Model reaction successfully realized with car diesel engine emissions. Abstract: A clean, safe, and efficient method for the N -carboxyalkylation of lactams was designed and studied in the current report. This three-component coupling of the substrate, carbon dioxide and an alkyl halide, has been developed as a green alternative to phosgene and chloroformates, and takes place at ambient temperature and low pressure of CO2 . This provided an improved protocol for the protection of cyclic amides and other functional groups and allowed the obtention of non-classical N -carboxyalkyl derivatives for which the corresponding chloroformates are not accessible or commercially available. The model reaction was successfully performed with car diesel engine emissions and opens the way for new perspectives of carbon capture and use solutions.